Inhibition of TWIST1 Leads to Activation of Oncogene-Induced Senescence in Oncogene Driven Non-Small Cell Lung Cancer - Burns, Timothy F. (2013)
A large fraction of non-small cell lung cancers (NSCLC) are dependent on defined oncogenic driver mutations. Although targeted agents exist for EGFR- and EML4-ALK-driven NSCLC, no therapies target the most frequently found driver mutation, KRAS. Furthermore, acquired resistance to the currently targetable driver mutations is nearly universally observed. Clearly a novel therapeutic approach is needed to target oncogene driven NSCLC. We recently demonstrated that the basic helix-loop-helix transcription factor Twist1 cooperates with mutant Kras to induce lung adenocarcinoma in transgenic mouse models and that inhibition of Twist1 in these models led to Kras-induced senescence. In the current study, we examine the role of TWIST1 in oncogene driven human NSCLC. Silencing of TWIST1 in KRAS mutant human NSCLC cell lines resulted in dramatic growth inhibition and either activation of a latent oncogene-induced senescence program or in some cases, apoptosis. Similar effects were observed in EGFR mutation driven and c-Met amplified NSCLC cell lines. Growth inhibition by silencing of TWIST1 was independent of p53 or p16 mutational status and did not require previously defined mediators of senescence, p21 and p27, nor could this phenotype be rescued by overexpression of SKP2. In xenograft models, silencing of TWIST1 resulted in significant growth inhibition of KRAS mutant, EGFR mutant and c-Met amplified NSCLC. Remarkably, inducible silencing of TWIST1 resulted in significant growth inhibition of established KRAS mutant tumors. Together these findings suggest that silencing of TWIST1 in oncogene driver dependent NSCLC represents a novel and promising therapeutic strategy.